The Making of China's Foreign Policy Towards Vietnam in the South China Sea Dispute: The Analysis of the Idiosyncratic Factors of Xi Jinping in Considering China's Strategic Environment (2012-2016) - Agung Banyu Perwita; Marella Putri (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2017)
The South China Sea dispute has its roots decades ago, but tensions have been increasing among the six claimants in recent years, based on each claimants own foreign policy claiming overlapping territory with each other and claimants conducting military activities in the area. Xi Jinping, the leader of the People’s Republic of China, takes a major role in making China’s foreign policy, including the territorial dispute in the South China Sea. Since his leadership, reportedly, more assertive measures had been taken by China, especially with Vietnam as one of the most vocal claimants. This paper explains China’s strategic environment focusing on China's foreign policy planks and U.S. Rebalance Policy in the Asia-Pacific, China’s foreign policy purpose in the South China Sea dispute, and finally analyzes how they are processed by Xi Jinping’s idiosyncratic factors in making the most rational decision of foreign policy towards Vietnam regarding the South China Sea dispute (2012–2016). This research finds that the influence of external parties in the region has resulted in Xi Jinping resorting to making foreign policy – from being assertive to more cooperative – which has the purpose of maintaining its bilateral relations with Vietnam as it is a rational decision to maintain China’s status quo in the dispute.Bahasa Abstrak: Perselisihan di Laut Tiongkok Selatan telah berakar sejak beberapa dekade yang lalu, namun ketegangan telah semakin meningkat  dalam beberapa tahun terakhir ini, dimana masing negara ‘claimants’ memiliki kebijakan luar negerinya sendiri untuk mengklaim wilayah yang saling tumpang tindih dan di saat bersamaan juga melakukan aktivitas  militer di daerah tersebut. Xi Jinping, Presiden RRT, memiliki peran yang sangat  besar dalam pembuatan kebijakan luar negeri Tiongkok, termasuk dalam perselisihan teritorial di Laut Tiongkok Selatan. Sejak kepemimpinannya, tindakan yang lebih tegas telah dilakukan oleh Tiongkok, terutama terhadap Vietnam sebagai salah satu penggugat yang paling vokal. Tulisan ini menjelaskan lingkungan strategis Tiongkok yang memfokuskan pada  kebijakan luar negeri Tiongkok dan Kebijakan “Rebalance” AS di Asia Pasifik, tujuan kebijakan luar negeri Tiongkok dalam perselisihan Laut Tiongkok Selatan, dan akhirnya menganalisis bagaimana faktor-faktor tersebut dipertimbangkan oleh Xi Jinping dalam pembuatan rasionalitas kebijakan luar negerinya terhadap Vietnam dalam perselisihan Laut Tiongkok Selatan (2012 - 2016). Tulisan ini menyimpulkan bahwa pengaruh pihak luar di wilayah tersebut telah mengakibatkan Xi Jinping beralih untuk membuat kebijakan luar negeri - dari bersikap asertif hingga lebih kooperatif - yang bertujuan untuk mempertahankan hubungan bilateralnya dengan Vietnam yang menjadi keputusan paling rasional untuk mempertahankan status quo Tiongkok dalam perselisihan tersebut.